Natural convection in a differentially heated enclosure having two adherent porous blocks saturated with a nanofluid; The European Physical Journal Plus; Vol. 132 - Astanina M. S. Marina Sergeevna; Sheremet M. A. Mikhail Aleksandrovich; Oztop H. F.; Nidal Abu-Hamdeh (2016, 2016)
Title screen